ANALISIS PENGARUH KEBIJAKAN SUBSIDI BIS DAMRI TERHADAP PENDAPATAN SOPIR ANGKUTAN UMUM TRAYEK MAPURUJAYA DISTRIK MIMIKA TIMUR KABUPATEN MIMIKA - Diva Pratiwi Sofia Yawauply (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2018)
Diva Pratiwi Sofia Yawauply (2018). Analysis of the Influence of Damri Bus Subsidy Policy on the Revenue of Public Transportation Driver in Mapurujaya Route, East Mimika District, Mimika Regency (Supervised by Mesak Iek and P. N. Patinggi) The aims of this research are: to find out and analyze differences in the income of public transport drivers before and after the implementation of Damri bus subsidies in the Mapurujaya route East Mimika District, Mimika regency. The data used in this research are qualitative data and quantitative data, which are sourced from public transport drivers in the Mapurujaya route, East Mimika District, Mimika Regency and the Mimika Regency BPS. Data was collected using methods of observation, interviews, questionnaires and documentation. To answer the formulation of this research problem, the analytical tool used is (paired t test). Based on the results of the analysis, it is known that: (a) The average income everyday of public transport drivers in the Mapurujaya route in the East Mimika District of Mimika Regency before the implementation of the Damri bus subsidy in the Mapurujaya East Mimika District Mimika Regency subsidy by the Mimika Regency Government was Rp. 551,966.7 ; (b) The average income everyday of a public transport driver on the Mapurujaya route in the East Mimika District of Mimika Regency after the implementation of the Damri bus subsidy in the Mapurujaya route East Mimika District Mimika Regency by the Mimika Regency Government is Rp. 396,366.7; (c) There is a significant income difference before and after the implementation of Damri bus subsidy in the Mapurujaya route East Mimika District, Mimika Regency, where the average income of public transport drivers in Mapurujaya East Mimika District Mimika regency after the Damri bus subsidy in Mapurujaya East Mimika District Mimika Regency is smaller than before the implementation of the Damri bus subsidy in the Mapurujaya East Mimika District Mimika regency.